(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Using annual time series data on the prevalence of anemia among pregnant women in Malaysia from 1990 – 2018, the study endeavors to make forecasts for the period 2017 – 2025. The study applies the Box-Jenkins ARIMA approach. The diagnostic ADF tests show that, W, the series under consideration is an I (2) variable. Based on the AIC, the study presents the ARIMA (1, 2, 1) model as the best model. The diagnostic tests further reveal that the presented model is basically stable, since its residuals are not serially correlated and are also normally distributed. The results of the study indicate that the prevalence of anemia among pregnant women in Malaysia will rise over the period 2017 – 2025, from about 38.1% in 2017 to approximately 49.6% by around 2025. The study generally calls for the need for the Malaysian government to expand on its nutritional supplementation policy in the female population as well as improving its antenatal care health system.